Traffic and operational characteristics of Kallang-Paya Lebar expressway tunnels - Chow, Fang Xiang. (2010)
Kallang Paya Lebar Expressway is Asia’s longest tunnel. Traffic incidents within the expressway are critical and can cause danger to the drivers. To minimize the danger of the incidents, KPE has done many safety measures. In this report, statistical analysis of the characteristics of the response time will be done on the Vehicle Recovery services (VRS) crews and LTA Traffic Marshals of KPE. The data are obtained during the author’s visit to the KPE operations center. Comparison of the mean response time will be conducted for different situations using t statistic hypothesis testing. The results achieved show that there are no differences in the mean response time during the peak hours compared to the off peak hours and weekends compared to weekdays. The availability of the Kallang Paya Lebar Expressway is computed based on the data for the month of February and May. With a ratio of availability 0.97 and 0.9, the KPE has more than 90% of the time operating in perfect conditions. There have been many incidents happening in the Kallang Paya Lebar Expressway. It is observed that there is little or weak correlation between the occurrence of each incident. There are no definite patterns and is unable to predict when accidents will happen based on the data.